Tantangan Pers Nasional Dalam Era Globalisasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Abstract: The purpose of this article is to help the Indonesian press in formulating obstacles it faces in making a success of globalization for the benefit of its audiences. This essay will show some adjustments the Indonesian press should make in order to empower its audiences. In this respect, the writer argues that the Indonesian press: (1) does not have to take media panics into consideration, especially with the increasingly rapid dissemination of information superhighway